PREPARING STUDENTS OF SMKN 7 KOTA SERANG FOR 21ST CENTURY WORK ENVIRONMENT THROUGH PJBL - Sanam, Sanam; Deni Ramdani, Sulaeman; Susanto, Triyo (Jurnal PTK dan Pendidikan, 2023)
The 21st-century work environment presents new challenges for education. Therefore, preparing students to face the 21st-century work environment requires innovative and relevant educational approaches. This study aims to analyze the preparation of SMKN 7 Serang City students in facing the 21st-century work environment through a project-based learning (PjBL) approach. This research uses a descriptive quantitative approach, data in the form of questionnaires are analyzed to identify teamwork, project management, communication skills, interpersonal skills, and problem-solving. The results showed that PjBL has made a positive contribution to improving students' 21st-century skills. Students involved in PjBL have a deeper understanding of the application of theoretical concepts in the context of the work environment. The conclusion is that PjBL is an effective learning method in preparing students of SMKN 7 Serang City for the 21st-century work environment. The results of this study confirm the importance of innovative approaches in vocational education to ensure students have skills and knowledge relevant to future developments.